2016
DOI: 10.37190/160213
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of natural organic matter removed from water along with its treatment

Abstract: The object of this study was to examine the nature of natural organic matter (NOM) removed on each stage of water treatment train used in the "Mokry Dwór" Wrocław Water Treatment Plant (WTP) and to compare obtained results with water treatment efficiencies achieved with the use of membrane ultrafiltration, ion-exchange and UF/ion-exchange integrated processes. In the experiments fractional analysis with the use of polymeric resins (DAX-8, XAD-4 and IRA-958) was used. Obtained results have shown that most (56%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…humic, fulvic and humic acids) and high molecular weight carboxylic acids [11]. Literature reports indicate that in water treated for drinking purpose, the content of the hydrophobic fraction may range from 56% to as much as 79% of DOC [3][4][5][6][7]11]. In the structure of both NOM fractions, fundamental differences are observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…humic, fulvic and humic acids) and high molecular weight carboxylic acids [11]. Literature reports indicate that in water treated for drinking purpose, the content of the hydrophobic fraction may range from 56% to as much as 79% of DOC [3][4][5][6][7]11]. In the structure of both NOM fractions, fundamental differences are observed.…”
Section: Resultsmentioning
confidence: 99%
“…Change in the content of NOM fraction in unit processes of the technological system. The research carried out by [11] showed that in the removal of dissolved organic compounds, the most effective was the coagulation process, where the removal of DOC in 40.1% was observed. The biofiltration process removed only 6.3% DOC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of removing organic pollutants on active carbon beds has been confirmed by numerous studies [15,19,[26][27][28][29]. Conventional water treatment systems eliminate natural organic substances up to 40% [11,21,24], while systems extended by biofiltration, depending on the time of biofilter exploitation, achieve from 24-100% [15,19,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%